PENGARUH KOMUNIKASI DAN KONFLIK KERJA TERHADAP KOMITMEN ORGANISASI PT. SURYA TARA JAYA MEDAN - Cynthia Tanadi; Syawaluddin Syawaluddin; Mila Asmawiani Okta (STIE-PMCI, 2020)
Abstract. Organizational commitment is: the attitude or form of employee behavior towards the organization in the form of loyalty and the achievement of the organization's vision, mission, values and goals. High commitment to employees can not be formed just like that, but it requires the application of management and appropriate actions by the company so that employees are comfortable in working and are willing to serve long periods of time such as by forming a good communication fabric and preventing work conflicts in company. The formulation of the problem in this study is the extent of the influence of communication and work conflict on organizational commitment of PT. Surya Tara Jaya Medan.The method used in this study is a survey approach, the type of research is quantitative descriptive and the nature of this research is descriptive explanatory. The population in this study are: permanent employees of PT. Surya Tara Jaya Medan as many as 61 employees. The sampling technique used in this study was: saturated sampling and totaling 61 employees. Data collection method is done by Likert scale. The model of data analysis used to answer hypotheses is multiple regression.The results showed that simultaneously Communication and Work Conflict had a positive and significant effect on the organizational commitment of PT. Surya Tara Jaya Medan and partially the most dominant influence is communication.Â Â Keywords: Communication, Work Conflict, Organizational Commitment